Communication Strategy On Students' Written Arabic Text - Pabiyah Toklubok @ Hajimaming; Nurhidayati Nurhidayati (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to describe how the communication strategy in student’s written text which included paraphrasing strategies, borrowing strategies and avoidance strategies. This research was a qualitative research with a socio-psycho-structural approach. The research data were verbal data in the form of data: (1) written fiction narrative, (2) interview transcription, and (3) observation notes. The data were analyzed by interactive analysis by Tarone’s comunication strategies. The result of the research showed that in solving the communication problem, Arabic language learners used the strategy based on the language between the Indonesia or the Javanese language, by generalizing the forms, creating paraphrases, creating words, and reconstructing sentences. Some of the communication strategies which were employed by learners were: (a) paraphrasing strategies, (b) borrowing strategies, and (c) avoidance strategies. Paraphrasing strategies were implemented through approximation techniques, creating or substituting word coinage, and using circumlocution. Borrowing strategies were done through the use of literal translation strategies, code mixes, requests for help, and use of mimic or gestures. Avoidance strategy was used through the process of avoidance of the use of language phrases that had not been properly mastered or avoid certain topics that would complicate the speaker in expressing the purpose of the speech.